Density of states of one-dimensional Pauli ionic conductor - Stasyuk, I.V.; Dulepa, I.R. (Condensed Matter Physics, 2007)
Microscopic one-dimensional noninteracting model for the description of the energy spectrum of the ion subsystem
in ionic conductor is considered. The processes of ionic hoppings are described in terms of Pauli operators. Time-dependent correlation functions (b(t)b⁺(0))j in Pauli operators are obtained using the exact numerical procedure known for time-dependent spin correlation functions. The frequency dependence of autocorrelation function J bb+(ω) is calculated and analysed at the wide range of temperatures. The frequency and temperature dependences of the one-particle density of states are investigated. Розглянуто мiкроскопiчну одновимiрну модель невзаємодiючих частинок для опису енергетичногоспектру iонної пiдсистеми в iонному провiднику. Процеси iонного перескоку описанi у термiнах операторiв Паулi. Використовуючи точний числовий метод, вiдомий для часових спiнових кореляцiйних функцiй, отримано часовi кореляцiйнi функцiї (b(t)b⁺(0))j в операторах Паулi. Обчислено i проаналiзовано частотну залежнiсть автокореляцiйної функцiї J bb+(ω) в широкому iнтервалi температур. Дослiджено частотну i температурну залежностi одночастинкової густини станiв.